Cross-Cultural Validation of the Portuguese from Portugal Version of the Test for Respiratory and Asthma Control in Kids (TRACK) Questionnaire - Leiria-Pinto, P (2021)
Introduction. The Test for Respiratory and Asthma Control in Kids (TRACK) is a tool to assess asthma control in preschool children. This study aims to validate the Portuguese from Portugal version of the TRACK questionnaire. Methods. A prospective cohort study was carried out to assess their psychometric characteristics. Caregivers of 141 children under age 5 with asthma symptoms were enrolled. Results. Internal reliability was close to 0.70 (Cronbach's α). The test-retest reliability was 0.87. TRACK scores were different between well, partially, and non-controlled asthma groups (p less than 0.001). Patients rated as having better control showed an increase in TRACK scores. Conclusions. The Portuguese version of the TRACK questionnaire is accurate and reliable for monitoring asthma control. Its use may help to overcome challenges with the management of this age group.